Building a Knowledge-Based Economy through “Sciencing”: The University of Abuja Students’ Experiences - Aregbesola1, B.G; Barau, Y; Abdulkarim, A (International Journal on Integrated Education, 2025)
This study explores building a knowledge-based economy through “sciencing”: the University of Abuja students’ experiences with a focus on developing critical thinking, problem-solving, and technical skills in students. The research aims to evaluate how "Sciencing" can better prepare students for STEM employment by fostering hands-on, inquiry-based learning experiences. Additionally, the study examines the role of university-industry collaborations in aligning academic curricula with industry needs, thereby contributing to Nigeria’s transition to a knowledge-based economy. It also investigates the importance of faculty professional development to support the effective implementation of "Sciencing" in teaching practices. A mixed-methods approach, combining quantitative and qualitative data, is employed to assess the impact of this approach on student learning outcomes and industry readiness. The findings revealed among others that students develop essential skills, such as critical thinking, problem-solving, and technical skills which are vital for success in STEM fields with the implementation of “Sciencing” This hands-on approach allows students to better connect theoretical concepts to real-world applications for knowledge based economy. Moreover, it strengthens university-industry partnerships, ensuring that curricula are more closely aligned with the evolving demands of the STEM workforce. The paper recommendations include ongoing faculty member development, increased collaboration with industry partners, and the integration of technology to further enhance experiential learning which fosters “Sciencing” approach.